(untitled) (Journal of Physical Education (Maringá), 2016)
This study aimed to investigate the anthropometric indicators and motor performance in young school. The variables selected were: body mass index (BMI), waist circumference (WC), ratio waist / height (RCEst) and Motor Performance (DM). For performance evaluation we used the Body Coordination Test for Children (KÃ¶rperkoordinationstest fÃ¼r Kinder - KTK). Data were analyzed from the descriptive and inferential statistics with p â‰¤0,05. Comparing DM relative to the weight status we observed significant differences between the overweight group and normal weight (p = 0.000) and underweight groups (p = 0.006). Comparing DM between groups in CC and RCEst variables were observed significant differences between normal groups (97.07 ± 12.87 and 97.50 ± 13.25 respectively) and health risk (92.26 ± 10.5 and 92.00 ± 9.58) (p = 0.001) (p = 0.000) respectivel . Thus, it can be to argued that changes in anthropometric indicators affect the DM of young school.